(untitled) (Journal of Applied Oral Science, 2013)
The side effects of chemotherapy on the lips may cause esthetic and functional impact and increase the risk of infection. HPA Lanolin® is an option for supportive therapy because it has anti-inflammatory, antimicrobial and moisturizing properties. Objective: To evaluate the efficacy of this product in the prevention of lip alterations in a population of patients undergoing chemotherapy. Material and Methods: Patients undergoing chemotherapy (n = 57) were examined and distributed into two groups: study (used HPA Lanolin®) and control (without supportive therapy on the lips). We evaluated the patients two weeks after chemotherapy, registering oral alterations, symptoms of pain, discomfort, limitation of mouth opening and dehydration, classified according to a visual analogue scale. Results: Patients who used HPA Lanolin® had lower dehydration and experienced improvement of lip dryness (p